Enhancing Social Inclusion of Children With Externalizing Problems Through Classroom Seating Arrangements: A Randomized Controlled Trial. (March 2018) - van den Berg, Y. H. M.; Stoltz, S.
Inclusive education has brought new challenges for teachers, including the search for a suitable place in the classroom for children with externalizing problems. In the current study, we examined whether a careful rearrangement of the classroom seats could promote social acceptance and more prosocial behaviors for children with externalizing problems, and limit the potential negative consequences for classmates sitting next to them. The sample of this randomized controlled trial consisted of 64 classrooms with 221 fourth- to sixth-grade children selected by their teachers because of elevated levels of externalizing behavior. Results showed that over time children with externalizing behavior were better liked by their seatmates and showed fewer externalizing problems according to the teacher. This was particularly the case when students sat next to a well-liked and prosocial buddy, or when they were initially disliked. Classmates who sat next to a child with externalizing problems did not become more aggressive or less prosocial over time. Yet their social status did decrease slightly over time as a result of the rearrangement. We discuss implications and future directions for research on classroom seating arrangements to support children with externalizing problems.